2010
DOI: 10.1086/653204
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Epidemiological Characteristics and Clinical Outcomes of Pandemic (H1N1) 2009 Influenza, Compared with Seasonal Influenza

Abstract: BACKGROUND There are limited data comparing the clinical presentations, comorbidities, and outcomes of patients with infections due to seasonal influenza with patients with infections due to pandemic (H1N1) 2009 influenza. OBJECTIVE To compare the epidemiological characteristics and outcomes of pandemic (H1N1) 2009 influenza with those of seasonal influenza. METHODS A cross-sectional study was conducted among patients who received diagnoses during emergency department and inpatient encounters at 2 affiliat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 30 publications
5
60
1
4
Order By: Relevance
“…Also, Li et al in 2011 in a their study reported that female subjects with influenza A are higher than males (20). Also, this point was reported by other researchers (21)(22)(23). And in Cao et al's study, male subjects were higher, however, Caini et al presented that sexes were equally distributed (15).…”
Section: Discussionmentioning
confidence: 85%
“…Also, Li et al in 2011 in a their study reported that female subjects with influenza A are higher than males (20). Also, this point was reported by other researchers (21)(22)(23). And in Cao et al's study, male subjects were higher, however, Caini et al presented that sexes were equally distributed (15).…”
Section: Discussionmentioning
confidence: 85%
“…To the Editor-As was reported recentiy in the journal by Shiley et al, 1 it is important to investigate the differences in clinical and epidemiological characteristics between pandemic and seasonal influenza. However, is interesting to describe the differences in nosocomial transmission.…”
Section: Rates Of Hospital-acquired Influenza Due To the Pandemic H1nmentioning
confidence: 99%
“…Prosečna životna dob bolesnika bila je 29,26 godina i znatno je niža nego u prethodnim sezonama, ali je slična onoj koja se za ovu sezonu navodi u drugim regionima sveta (11)(12)(13)(14). nagli pad broja obolelih starijih od 60 godina života objašnjava se činjenicom da su te osobe tokom svog života (najverovatnije u detinjstvu, 1957. godine), došle u kontakt sa agensom koji je genetski sličan novom virusu gripa, i tom prilikom stvorile zaštitna antitela, koja ih sada štite od infekcije (15).…”
Section: Slika 3 Odeljenja Na Kojima Su Lečeni Pacijenti Oboleli Od unclassified
“…iz dostupnih literarnih podataka vidimo da je često ispitivana uloga prethodnih bolesti ili stanja na pojavu težih kliničkih formi gripa koje su zahtevale bolničko lečenje. najviše je ispitivano učešće oboljenja respiratornog sistema, posebno astme, bolesti kardiovaskularnog sistema, dijabetesa, gojaznosti, hronične bolesti srca i imunosupresije (14,(22)(23)(24). u našem ispitivanju, od prisutnih koomorbiditeta kod hospitalizovanih pacijenata registrovane su: bronhijalna astma (7,67%), dijabetes (5,21%), hronične bolesti pluća (4,60%), bolesti kardiovaskularnog sistema (4,29%), bolesti nervnog sistema (3,99%) i karcinomi (0,31%), a neretko je kod iste osobe utvrđeno postojanje i dve bolesti.…”
Section: Slika 3 Odeljenja Na Kojima Su Lečeni Pacijenti Oboleli Od unclassified